Specialization in entry-level products : a strategy for industrial development in Africa - (:unkn) unknown (My University, 2019)
This article analyzes the potential of industrial development in Africa. Starting with the observation that the domestic demand in Africa is mainly oriented towards entry-level products, we explore the advantages of an industrialization strategy aimed at manufacturing these products. After identifying the determinants of specialization in entry-level products, we find that these product lines can play a fundamental role in the industrialization of Africa. It should also be noted that studies on entry-level products in Africa are quite rare; this study therefore opens up avenues for future research.
Keywords: African Research